Implementation of differentiated learning to improve critical thinking in elementary school students - Siti Fatimah; Fathur Rokhman; Suwito Eko Pramono; Bambang Subali; Nuni Widiarti (Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are one of the key 21st-century skills that need to be developed from primary education onwards, requiring a learning approach tailored to students' needs and characteristics, one of which is differentiated learning. This study aims to analyse the application of differentiated learning in developing critical thinking skills in elementary school students, identify the challenges of its implementation, and explore learning adaptation strategies during the 2020–2024 period. The study used a qualitative approach with a systematic review method of relevant national and international journal articles, which were collected through structured literature searches, selected based on specific criteria, and analysed thematically. The results of the study show that differentiated learning generally contributes positively to increasing student engagement, conceptual understanding, and critical thinking skills because it allows teachers to tailor learning to the readiness, interests, and learning styles of students. However, its implementation still faces various obstacles, such as limitations in teachers' pedagogical competencies, planning time, and learning facility support, especially in the context of online and hybrid learning. This study concludes that differentiated learning has great potential as an adaptive learning strategy in improving the critical thinking skills of elementary school students. Therefore, policy support, ongoing training, and professional guidance are needed to ensure optimal and sustainable implementation.